Comparative Study of Numerical and Experimental Analysis of Micro Hydro Power Plant in Nagari Koto Hilalang Solok Regency - Khairuni Delfi Anisa; Arwizet K; Remon Lapisa; Mulianti Mulianti (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
Indonesia has the potential to produce large amounts of electrical energy by utilizing sustainable energy, especially water energy. There are still many areas that are far from urban areas that do not have electricity, especially remote areas. One of them is Nagari Koto Hilalang, Solok Regency, which has built a Micro Hydro Power Plant (PLTMH). The purpose of this research was to determine the capacity and potential of PLTMH in Nagari through simulation. This research uses the Computational Fluid Dynamics (CFD) simulation method with the Ansys Fluent 2021 R2 Student Version software. The magnitude velocity simulation values for the inlet velocity 12.44 m/s, 13.28 m/s, and 13.65 m/s produce different maximum values for the runner. The resulting torque has a value of 110.5 Nm. The exact output power generated by the Ansys simulation has a value of 10.78 kW. The efficiency of the turbine with a power of 10.78 kW obtained from the simulation results is 66%. Indonesia memiliki potensi untuk menghasilkan energi listrik yang besar dengan memanfaatkan energi yang berkelanjutan terutama energi air. Masih banyak daerah yang jauh dari perkotaan belum teraliri oleh listrik terutama daerah terpencil. Salah satunya Nagari Koto Hilalang, Kabupaten Solok yang sudah dibangun Pembangkit Listrik Tenaga Mikro Hidro (PLTMH). Tujuan dari penelitian ini adalah untuk mengetahui kapasitas dan potensi PLTMH yang ada di nagari tersebut melalui simulasi. Penelitian ini menggunakan metode simulasi Computational Fluid Dynamics (CFD) dengan software Ansys Fluent 2021 R2 Student Version. Nilai simulasi kecepatan magnitude untuk velocity inlet 12,44 m/s, 13,28 m/s dan 13,65 m/s menghasilkan nilai maksimum yang berbeda pada runner. Torsi yang dihasilkan memiliki nilai 110,5 Nm. Daya luaran yang tepat yang dihasilkan oleh simulasi Ansys memiliki nilai 10,78 kW. Efisiensi pada turbin dengan daya 10,78 kW yang didapat dari hasil simulasi yaitu 66%.